A QUASI-EXPERIMENTAL STUDY ON THE EFFECTS OF A SELF-REGULATION-BASED ESL WRITING INSTRUCTIONAL MODULE ON MALAYSIAN SECONDARY SCHOOL STUDENTS’ ESL WRITING PERFORMANCE - Jacinta Karen Juin; Wardatul Akmam Din; Ameiruel Azwan Ab Aziz; Suyansah Swanto (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Self-regulation is a necessary component of developing skilled writers. Self-regulation, on the other hand, is rarely discussed in Malaysian ESL contexts, particularly in terms of ESL writing. This quasi-experimental study evaluated an ESL writing instructional module based on self-regulation with the goal of improving secondary school students’ narrative writing. This study, which was conducted as part of a larger study, presented the results of the pilot study. The findings indicated statistically significant improvements in the students’ overall writing performance and in each of the four components of writing, namely content, communicative appropriateness, organisation, and language. The findings indicated that the self-regulation-based writing instructional module was effective at improving students’ overall writing performance and performance in each of the four writing aspects. Future studies should include a larger sample size, extend the duration of the intervention, and investigate additional variables such as gender and level of proficiency.